Acute encephalitis syndrome - Sibabratta Patnaik; Shrishu R. Kamath; Mukesh Kumar Jain (Wolters Kluwer Medknow Publications, 2024)
Acute encephalitis syndrome (AES) is a serious disorder characterized by the sudden onset of inflammation in the brain, which may lead to life-threatening clinical situations. This syndrome encompasses a range of neurological disorders, including, but not limited to, viral and bacterial infections, toxins, and metabolic causes. It includes a wide array of spectrum of diseases, and diagnosis is based on clinical symptoms and a wide range of investigations. Treatment is usually symptomatic, and in some instances, definitive treatment is available. Long-term sequelae of AES can include cognitive deficits, behavioral changes, motor impairments, and epilepsy. Rehabilitation and supportive care are often necessary.